Challenges of entrepreneurship development in Europe in the light of the pandemic crisis - Remeikienė, Rita; Gasparėnienė, Ligita; Fedajev, Aleksandra; Arsić, Sanela; Noga, Gracjana (Journal of Business Economics and Management, 2023)
The paper aims to perform an objective comparative analysis of the business climate for entrepreneurship development in European countries in 2021 and group them according to the quality of the business climate. The research uses thirteen criteria from the Global Entrepreneurship Monitor report and TOPSIS methodology combined with entropy to perform a comparative analysis of the business climate for entrepreneurship development in selected European economies in 2021. Usage of TOPSIS and entropy method based on the last available data enabled objective and the most accurate evaluation and ranking of countries, taking into account all observed criteria. According to the study, the ranking of European economies indicates that the Netherlands has the most favorable business climate for entrepreneurship development, considering all observed criteria, while Belarus is ranked in the last position. According to relative closeness to the ideal solution (Ci*), the four clusters of countries are derived. Besides the Netherlands, Lithuania, Norway, and Finland were also dedicated to the first cluster, indicating that these economies obtained the most favorable conditions for entrepreneurship development during the pandemic crisis. On the other hand, former command economies and Greece and Cyprus are placed in Cluster IV since they haven’t supported entrepreneurs with sufficient and appropriate economic policy and regulatory reforms.